Genotype and phenotype classification of 29 patients affected by Krabbe disease - Madsen, Anna M. H. (JIMD Rep, 2019)
Krabbe disease is a rare neurodegenerative lysosomal storage disorder caused by mutations in the galactocerebrosidase gene, GALC. Krabbe disease usually affects infants, but has also been reported in older children and adults. Different phenotypes are described based on age at onset. The gene encoding the galactocerebrosidase enzyme was cloned and expressed in 1993, and up until today 117 mutations have been described. In a patient population of Northern European origin, a 30‐kb deletion and two missense mutations, c.1586C>T; p.T529M and c.1700A>C; p.Y567S, are expected to account for 50%‐60% of pathogenic alleles. In this study, we present information on genetic variation, enzyme activity, and phenotypes of 29 patients affected by Krabbe disease. Patient data were collected from patient files at the Department of Clinical Genetics, Rigshospitalet. Ten previously unreported mutations were identified, including four missense mutations; c.1142C>T; p.T381I, c.596G>T; p.R199M, c.443G>A; p.G148E, c.1858G>A; p.G620R, two nonsense mutations; c.863G>A; p.W288*, c.1214c>G; p.S405*, one splice site mutation; c.442+1G>A, one insertion; c.293insT and two deletions; c.1003_1004del, c.887delA. For all of the new mutations, we were able to classify them in phenotype groups. Furthermore, we present a combined allele frequency of the three frequent mutations p.T529M, p.Y567S, and the 30‐kb deletion of 62%, and we describe a broadening of the phenotypes associated with the mutations p.T529M and p.Y567S.